Design Thinking for Textiles: let's make it meaningful. (28th July 2017) - Valentine, Louise; Ballie, Jen; Bletcher, Joanna; Robertson, Sara; Stevenson, Frances
Abstract: The values underpinning the global textile industry are continuing to transform because of globalisation, sustainability and technological progress. This is enabled by the changes within the discipline of design itself, through the impact of design thinking on business management and leadership (Cooper et al, 2015), a move towards co-creation rather than individual authorship (Sanders, 2013; Sanders and Stappers, 2014), smart technologies (Taylor and Robertson, 2014), and greater attention to how we meet today's social needs through design (Thackera, 2013; Manzini, 2015). This paper is concerned with the impact of transformation upon the role of the textile designer and design educator. Discussion draws on recent design research in Smart Textiles, E-Co Textiles and the sustainability agenda, future craft and designer's thinking, revealing a set of values underpinning the contemporary craft of textile design, facilitating a conversation as to how they relate to the active concept of authenticity.